2009 3rd IEEE International Conference on E-Learning in Industrial Electronics (ICELIE) 2009
DOI: 10.1109/icelie.2009.5413213
|View full text |Cite
|
Sign up to set email alerts
|

CAD in engineering education: Getting the balance right

Abstract: Many engineering technology programmes use industry-standard computer-aided design (CAD) tools to enhance traditional teaching methods and to provide students with the necessary CAD skills as required by industry. In addition, technology driven initiatives such as e-learning and virtual laboratories provide the educator with an exciting range of tools and instruments intended to bring about a deeper understanding of complex phenomena. These tools are commonly used in conjunction with traditional classroom lect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…Due to the scarce time available for teaching the use of CAD tools in educational plans, some authors have promoted the use of Web-based systems to improve CAD training [49,66], or the combination of off-line and online classes [36]. In this sense, Kallis and Fritz [42] analysed the e-learning tools available for learning CAD and concluded that engineering students have come to accept their use as an essential tool during their engineering training. Another alternative is the use of multimedia tools to complete and support the CAD pedagogy [4].…”
Section: Cad Learningmentioning
confidence: 99%
“…Due to the scarce time available for teaching the use of CAD tools in educational plans, some authors have promoted the use of Web-based systems to improve CAD training [49,66], or the combination of off-line and online classes [36]. In this sense, Kallis and Fritz [42] analysed the e-learning tools available for learning CAD and concluded that engineering students have come to accept their use as an essential tool during their engineering training. Another alternative is the use of multimedia tools to complete and support the CAD pedagogy [4].…”
Section: Cad Learningmentioning
confidence: 99%
“…McLaren (2008) combina el Dibujo Técnico manual del siglo XXI y el uso de instrumentos CAD. Kallis & Fritz (2009) pretenden mejorar los métodos de enseñanza para que los alumnos consigan las habilidades necesarias en CAD requeridas en la industria, mediante herramientas que son proporcionadas por los laboratorios virtuales. Liang (2009) resuelve modelados geométricos para el aprendizaje basado en un método de realidad virtual utilizando 3D Studio Max®.…”
Section: Evolución Histórica De Las Técnicas De Representación Gráficaunclassified